The association between red cell distribution width to total calcium ratio and syntax score in patients with acute coronary syndrome - Küçük, Uğur (Journal of Surgery and Medicine, 2020)
Aim: The relationship of both red blood cell distribution width (RDW) and Syntax risk score with prognosis and mortality in patients with acute coronary syndrome (ACS) has been shown. Besides, there is insufficient information about the use of red cell distribution width to total serum calcium (RDW-to-TSC) ratio in patients with ACS. We aimed to research the relationship between RDW-to-TSC and Syntax risk scores in our study. Methods: For our retrospective cohort study, 270 patients hospitalized in the cardiology intensive care unit with the diagnosis of myocardial infarction between January 2019 and December 2019 were screened. A total of 115 patients who were eligible were included in the study. The patients were classified into two groups: 58 had NSTE-ACS and 57 had STEMI. The included age range was 18-80 years. RDW-to-TSC was calculated as the ratio of red cell distribution width to total serum calcium count. By using Pearson’s correlation analysis, the relationship between RDW-TAF ratio and Syntax score was obtained. Results: Among 115 patients, there were 50 males (43.5%), and 65 females (56.5%). The mean age was 58.09 (9.55) years. There were more hypertensive patients in the NSTE-ACS group (P=0.003). There was no statistically significant difference in RDW-to-TSC ratio between the two groups (P=0.809). The correlation of RDW and RDW / TSC ratio with syntax score were statistically significant (P<0.001). Conclusions: RDW-to-TSC ratio is a simple, cost-effective, and readily available test in all health centers. This may be used as a risk calculation tool like the Syntax score for patients with ACS.